Disain dan Validitas E-Instrument Five Tier-Multiple Choice Test Menggunakan iSpring Quiz Maker Sebagai Asesmen Literasi Sains Siswa Pada Pembelajaran Abad-21 - Fatni Mufit; Hendra Musfa Dirman (Jurnal Penelitian Pendidikan IPA, 2022)
The goal of 21st century learning is to provide students with conceptual knowledge and scientific literacy abilities. Creating a five-tier multiple choice e-instrument on the subject of work and energy and momentum and impulse. The purpose of this study was to determine the characteristics and validity of a five-tier multiple choice e-instrument using the i-Spring Quiz Maker as an assessment of scientific literacy and understanding of concepts for high school students in class X. The research carried out included the type of development research using the Plomp model. The research was carried out to the expert review stage (Validity). The object of the research is a five-tier multiple choice e-instrument using the i-Spring Quiz Maker. The source of content validity data was obtained from the results of expert validation by a Physics lecturer at the Faculty of Mathematics and Natural Sciences, UNP. Preliminary research conducted at this stage of research revealed that teachers were not familiar with the five-tier-multiple choice instrument in assessing students' conceptual understanding, especially on the matter of effort and energy and momentum and impulse. In the Development or Prototyping Phase, a five-level multiple choice electronic instrument is designed using the i-Spring Quiz Maker application. The results of the self-evaluation were obtained with very good criteria. The results of the instrument validity test are obtained as a whole with a high validity category.